Untersuchung des Füllverhaltens holzfaserverstärkter Kunststoffe (WPC) mit hohen Füllstoffgehalten - Flachmann, Felix

Simulationsgestützte Bestimmung und Optimierung der Mischgüte in der Einschneckenextrusion - Frank, Maximilian

Construction of A-stable explicit last-stage diagonal implicit Runge–Kutta (ELDIRK) methods - Mahnken, Rolf; Westermann, Hendrik (Computational Mechanics)
ELDIRK methods are defined to have an Explicit Last stage in the general Butcher array of Diagonal Implicit Runge-Kutta methods, with the consequence, that no additional system of equations must be solved, compared to the embedded RK method. Two general formulations for second- and third-order ELDIRK methods have been obtained recently in Mahnken [21] with specific schemes, e.g. for the embedded implicit Euler method, the embedded trapezoidal-rule and the embedded Ellsiepen method. In the first part of this paper, we investigate some general stability characteristics of ELDIRK methods, and it will be shown that the above specific RK schemes are not A-stable. Therefore, in the second part, the above-mentioned general formulations are used for further stability investigations, with the aim to construct new second- and third-order ELDIRK methods which simultaneously are A-stable. Two numerical examples are concerned with the curing for a thermosetting material and phase-field RVE modeling for crystallinity and orientation. The numerical results confirm the theoretical results on convergence order and stability.
Keywords: Applied Mathematics; Computational Mathematics; Computational Theory and Mathematics; Mechanical Engineering; Ocean Engineering; Computational Mechanics

Anisotropic Mechanical and Microstructural Properties of a Ti-6Al-7Nb Alloy for Biomedical Applications Manufactured via Laser Powder Bed Fusion - Milaege, Dennis; Eschemann, Niklas; Hoyer, Kay-Peter; Schaper, Mirko (Crystals)
Through tailoring the geometry and design of biomaterials, additive manufacturing is revolutionizing the production of metallic patient-specific implants, e.g., the Ti-6Al-7Nb alloy. Unfortunately, studies investigating this alloy showed that additively produced samples exhibit anisotropic microstructures. This anisotropy compromises the mechanical properties and complicates the loading state in the implant. Moreover, the minimum requirements as specified per designated standards such as ISO 5832-11 are not met. The remedy to this problem is performing a conventional heat treatment. As this route requires energy, infrastructure, labor, and expertise, which in turn mean time and money, many of the additive manufacturing benefits are negated. Thus, the goal of this work was to achieve better isotropy by applying only adapted additive manufacturing process parameters, specifically focusing on the build orientations. In this work, samples orientated in 90°, 45°, and 0° directions relative to the building platform were manufactured and tested. These tests included mechanical (tensile and fatigue tests) as well as microstructural analyses (SEM and EBSD). Subsequently, the results of these tests such as fractography were correlated with the acquired mechanical properties. These showed that 90°-aligned samples performed best under fatigue load and that all requirements specified by the standard regarding monotonic load were met.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

Herstellung und Charakterisierung von Wood-Plastic-Composites (WPC) mit einer Matrix aus thermoplastischen Polyurethanen zur Erzeugung einer Holz-WPC-Verbundstruktur - Richters, Maximilian

Ein Beitrag zur Erarbeitung von Fertigungsrichtlinien für das Kunststoff Freiformen - Hirsch, Andre

Materialschonende Verarbeitung von Thermoplasten auf Wave-Schnecken - Schall, Christoph Wilhelm Theodor

Experimentelle und simulative Analyse der Mischwirkung in Einschneckenextrudern - Schadomsky, Michael

Evaluation of the Influence of Particle Type, Shape and Size on the Thermal Conductivity of Filled Polymers in the Fused Filament Fabrication Process - Moritzer, Elmar; Elsner, Christian Lennart
The Fused Filament Fabrication (FFF) process is increasingly used for the manufacturing of individualized and complex structures, which continuously results in new requirements regarding the material properties. A characteristic material property for polymers is the low thermal conductivity. However, for specific applications, such as additively manufactured injection molding tool inserts, increased thermal conductivity is advantageous. In this study, the influence of fillers of different types, shapes and sizes on the resulting thermal conductivity of compounds is investigated. The aim is to analyze the effects of the fillers, considering the FFF-typical strand structure. The first step is to characterize the fillers in terms of shape and size. Based on this, the resulting thermal conductivity of specimens manufactured in the FFF process for different build orientations is specifically examined and compared to injection molding. This ensures that the process- and material-related anisotropy of the specimens is considered in the analysis. For the evaluation, a methodology is developed to be applied in Laser Flash Analysis (LFA), which allows the results to be evaluated despite the characteristic FFF surface structure. For the final visualization of the influence of the particle size on the particle orientation, Scanning Electron Microscopy (SEM) images of the relevant polymer compounds are made. The investigations provide a data basis regarding the influence of the particle type, shape and size on the thermal conductivity as well as for the requirement-oriented selection of fillers for processing thermally conductive polymer compounds in the FFF process.

Ein Beitrag zur Steuerung der Faserstaubentwicklung faserverstärkter Kunststoffe beim mechanischen Recycling - Tölle, Lisa

Mesh‐ and model adaptivity for NTFA and full‐field elasto‐plastic homogenization based on downwind and upwind approximations - Tchomgue Simeu, Arnold; Mahnken, Rolf (PAMM)
Abstract To increase the quality of computational results for heterogeneous materials like fiber‐reinforced composites with Prandtl–Reuss‐type material laws, goal‐oriented measures of the adaptive finite element method coupled to model adaptivity is established. The former is an adaptive mesh refinement on the macroscale, which allows to control the spatial discretization errors. The latter is an efficient combination of a numerically low cost nonuniform transformation field analysis (NTFA) and numerically high cost full‐field elasto‐plastic homogenization methods on the microscale. The present contribution deals with the application of the concept of downwind and upwind approximations to a goal‐oriented a posteriori error estimator based on duality techniques by means of reduced order homogenization schemes like NTFA, and with accuracy and numerical efficiency of the proposed goal‐oriented adaptive framework. NTFA consists of an offline phase and an online phase. During the offline phase, some relevant information of the micro system under consideration is precomputed allowing a reduced set of equations to be solved in the online phase. Thus, NTFA leads to a quite efficient homogenization method but less accurate compared to the full‐field homogenization method which is characterized with a high computational demand for accounting nonlinear microstructural mechanisms. Due to nonlinearities and time‐dependency of plasticity, the estimation of error transport and error generation are obtained with a backward‐in‐time dual method despite a high demand on memory capacity. In this contribution, the dual problem is solved with a forward‐in‐time dual method that allows estimating the full error during the resolution of the primal problem without the need for extra memory capacity. Several numerical examples illustrate the effectiveness of the proposed adaptive approach based on downwind and upwind approximations.

Uniaxial and biaxial experimental investigation of glassy polymers - Hamdoun, Ayoub; Mahnken, Rolf (Polymer)

A large deformation gradient theory for glassy polymers by means of micromorphic regularization - Hamdoun, Ayoub; Mahnken, Rolf (Archive of Applied Mechanics)
Abstract Cold forming of polycarbonate films results in the formation of shear bands in the necking zone. The numerical results obtained from standard viscoplastic material models exhibit mesh size dependency, requiring mathematical regularization. For this purpose, we present in this work a large deformation gradient theory for a viscoplastic isotropic material model published before. We extend our model to a micromorphic model by introducing a new micromorphic variable as an additional degree of freedom along with its first gradient. This variable represents a microequivalent plastic strain. The relation between the macroequivalent plastic strain and the micromorphic variable is accomplished by a micromorphic coupling modulus. This coupling forces proximity between the macro- and microvariables, leading to the targeted regularization effect. The micromorphic model is implemented as a three-dimensional initial boundary value problem in an in-house finite element tool. The analysis is performed for both uniaxial and biaxial specimens. The provided numerical examples show the ability of our model to regularize shear bands within the specimens and address the issue of localization.

Downwind and upwind approximations for primal and dual problems of elasto-plasticity with Prandtl–Reuss type material laws - Mahnken, Rolf; Tchomgue Simeu, Arnold (Computer Methods in Applied Mechanics and Engineering)

Characterization of Interfacial Corrosion Behavior of Hybrid Laminate EN AW-6082 ∪ CFRP - Delp, Alexander; Wu, Shuang; Freund, Jonathan; Scholz, Ronja; Löbbecke, Miriam; Tröster, Thomas; Haubrich, Jan; Walther, Frank (Materials)
The corrosion behavior of a hybrid laminate consisting of laser-structured aluminum EN AW-6082 ∪ carbon fiber-reinforced polymer was investigated. Specimens were corroded in aqueous NaCl electrolyte (0.1 mol/L) over a period of up to 31 days and characterized continuously by means of scanning electron and light microscopy, supplemented by energy dispersive X-ray spectroscopy. Comparative linear sweep voltammetry was employed on the first and seventh day of the corrosion experiment. The influence of different laser morphologies and production process parameters on corrosion behavior was compared. The corrosion reaction mainly arises from the aluminum component and shows distinct differences in long-term corrosion morphology between pure EN AW-6082 and the hybrid laminate. Compared to short-term investigations, a strong influence of galvanic corrosion on the interface is assumed. No distinct influences of different laser structuring and process parameters on the corrosion behavior were detected. Weight measurements suggest a continuous loss of mass attributed to the detachment of corrosion products.

The new TISTRAQ process: Solution treatment with rapid quenching and annealing for Ti-6Al-4V sheet metal part forming - investigation on heat transfer coefficient and influence on cooling rates - Kaiser, Maximilian Alexander; Höschen, Fabian; Pfeffer, Nina; Merten, Mathias; Meyer, Thomas; Marten, Thorsten; Rockicki, Pawel; Höppel, Heinz Werner; Tröster, Thomas (IOM3. Chapter 14: Forming, Machining & Joining [version 1; not peer reviewed])
Within the current energy and environmental crisis, new material- and energy-saving processes are needed. For this reason, this study focuses on the development of a new forming technology for Ti-6Al-4V sheet metal. It is based on combination of solution treatment by resistive heating with rapid tool-based quenching and subsequent annealing. This new “TISTRAQ” process is comparable with press-hardening already known for steels and hot die quenching known for aluminium alloys. One of the main influencing factors for this process is the heat transfer coefficient (HTC). It is an important driver for adjustment of basic parameters, as selection of tool material or the forming speed but also plays an important role while elaborating temperature distribution in the numerical model. Therefore, a new and unique test rig was developed to determine the HTC and to perform tool-based heat treatment at specimen level under laboratory conditions. The test rig was used to investigate the influence of the titanium-tool-lubricant system on HTC and cooling rate. Further the effect of heat treatment in the test rig and tool-based quenching on microstructure and mechanical properties was studied. To improve the prediction of the temperature distribution of the titanium during cooling, the HTC was integrated into the numerical process simulation
Keywords: Interfacial heat transfer coefficient; Ti-6Al-4V; nonisothermal forming; thermomechanical processing; TISTRAQ process

The new TISTRAQ process: Solution treatment with rapid quenching and annealing for Ti-6Al-4V sheet metal part forming - the effect of processing parameters on microstructure and mechanical properties - Pfeffer, Nina; Kaiser, Maximilian Alexander; Meyer, Thomas; Göken, Mathias; Höppel, Heinz Werner (IOM3. Chapter 14: Forming, Machining & Joining [version 1; not peer reviewed])
The phase and TTT diagrams of the Ti-6Al-4V system allow the development of a new forming process for a more energy- and materialefficient production of sheet metal parts. This new “TISTRAQ” process is composed of two steps. In terms of process technology, the first step is comparable to a direct press-hardening process already well known for steels. In this step, the Ti-6Al-4V sheet material is resistively heated to a temperature below β-transus Tβ and, after a very short holding time, simultaneously formed and quenched by use of water cooled tools. Thereby, the β phase undergoes a martensitic transformation. The second step is a subsequent short-time annealing, which leads to a hardening of the material. In this work, a new test rig using resistive heating technique was used in order to produce different solution treated and tool quenched (STQ) and subsequently annealed (STA) states. In this paper, the effects of heating rate, solution treatment temperature and holding time on microstructure and mechanical properties are addressed. For the characterisation, tensile testing and scanning electron microscopy were used. By the systematic variation of applied processing parameters, dominating effects on microstructure and mechanical properties were evaluated. For example, the solution treatment temperature was found to have a significant effect on microstructural features and characteristic strength and strain values. The obtained results reveal a high potential for future technical applications.
Keywords: Ti-6Al-4V; thermomechanical processing; resistive heating; quench-forming; process parameter-microstructure-properties relationship

The Influence of Ultrasonic Irradiation of a 316L Weld Pool Produced by DED on the Mechanical Properties of the Produced Component - Lehnert, Dennis; Bödger, Christian; Pabel, Philipp; Scheidemann, Claus; Hemsel, Tobias; Gnaase, Stefan; Kostka, David; Tröster, Thomas (Crystals)
Additive manufacturing of metallic components often results in the formation of columnar grain structures aligned along the build direction. These elongated grains can introduce anisotropy, negatively impacting the mechanical properties of the components. This study aimed to achieve controlled solidification with a fine-grained microstructure to enhance the mechanical performance of printed parts. Stainless steel 316L was used as the test material. High-intensity ultrasound was applied during the direct energy deposition (DED) process to inhibit the formation of columnar grains. The investigation emphasized the importance of amplitude changes of the ultrasound wave as the system’s geometry continuously evolves with the addition of multiple layers and assessed how these changes influence the grain size and distribution. Initial tests revealed significant amplitude fluctuations during layer deposition, highlighting the impact of layer deposition on process uniformity. The mechanical results demonstrated that the application of ultrasound effectively refined the grain structure, leading to a 15% increase in tensile strength compared to conventionally additively manufactured samples.

Non-rotationally symmetric joints – Mechanisms and load bearing capacity - Devulapally, Deekshith Reddy; Martin, Sven; Tröster, Thomas (Materials Research Proceedings)
Abstract. Traditionally, joints are cylindrical and rotationally symmetric. In the present study, non-rotationally symmetric joints are used for joining steel and Glass mat-reinforced thermoplastic sheets (GMT). In addition, the study also analyzes the impact of non-rotational symmetric joint rotation on the load-bearing capacity. Single lap joint specimens were fabricated using the In-Mold assembly technique for joining steel sheets with GMT. Tensile shear tests were performed on different orientations of the joint geometry, and it was observed that changing the joint orientation influences the load-bearing capacity. The joints are constitutively modeled using beam elements and the influence of joint rotation on load distribution is examined through a static simulation study.

Corrosion fatigue behavior of nanoparticle modified iron processed by electron powder bed fusion - Wackenrohr, Steffen; Torrent, Christof Johannes Jaime; Herbst, Sebastian; Nürnberger, Florian; Krooss, Philipp; Frenck, Johanna-Maria; Ebbert, Christoph; Voigt, Markus; Grundmeier, Guido; Niendorf, Thomas; Maier, Hans Jürgen (npj Materials Degradation)
Abstract Due to its excellent biocompatibility, pure iron is a very promising implant material, but often features corrosion rates that are too low. Using additive manufacturing and modified powders the microstructure and, thus, the material properties, e.g., the corrosion properties, can be tailored for specific applications. Within the scope of this study, pure iron powder was modified with different amounts of CeO 2 or Fe 2 O 3 nanoparticles and subsequently processed by Electron Beam Powder Bed Fusion (PBF-EB/M). The corrosion-fatigue behavior of CeO 2 and Fe 2 O 3 modified iron was investigated using rotation bending tests under the influence of simulated body fluid (m-SBF). While the modification using Fe 2 O 3 showed reduced fatigue and corrosion-fatigue strengths, it could be demonstrated that the modification with CeO 2 is characterized by improved fatigue properties. The superior fatigue properties in air are attributed to the positive impact of dispersion strengthening. Additionally, an increased degradation rate compared to pure iron could be observed, eventually promoting an earlier failure of the specimens in the corrosion fatigue tests.